The impact of dual-class creation on shareholder wealth - Noe, T; Jeong, J (1993)
This study compares the announcement effects of dual class recapitalization across insider holdings. We find positive announcement effects for the lowest insider holding firms and negative announcement effects for the firms whose insider holdings is near 50%. The evidence supports the hypothesis that there is an optimal level of insider holdings in the firm.